Capturing the object behaviour for storage system evaluation. (3rd January 2011) - Li, Chun-Hua; Zhou, Ke; Feng, Dan
In this paper, we present a kind of distributed tracing system for evaluating the performance of object storage system. The tracing build on the object-based Lustre file system can capture the object information synchronously from three subsystems of Lustre cluster file system. To improve I/O performance and efficiency, we utilise a queue and a FIFO buffer area to store trace data which is finally written out to a trace file by an output driver. In particular, we use some database tables to save the final integrated traces for convenient post-analysis. We have implemented and evaluated a prototype object tracing system on Linux which patched with Lustre 1.4.5 custom kernel patches. Our evaluation shows a low overhead tracing system.